THE JOCKEYS: THE ATHLETE FROM XIX CENTURY AND HIS STATUS IN THE SPORTS FIELD (Fiep Bulletin - online, 2015)
Melo's studies  (2001) show that the turf was the first sport to have a structure in Brazil, at Rio de Janeiro, by the XIX century. The first club was founded in 1849 (The Racing Club),  and the horseracings gained a structure vary fast, following the sport model from Europe, the existence of professional athletes included, the jockeys, responsible for conducting the horses in the contests. What is the characteristic of these athletes in XIX century? What kind of status were they given? What are the peculiarities of its organization? This study aims to discuss the presence and role of the jockeys in the pioneer structure of the Brazilian sports field, having as investigation locus the Rio de Janeiro turf from XIX century. This study helps us to understand the beginning of some dimensions found up to the present in the discourses regarding the sports.
Keywords: History of the Sports; turf; jockeys.